Energy Transition in South America: Elite S Views in the Mining Sector, Four Cases Under Study - Parker-Gumucio, C (Universidade Estadual de Campinas, 2018)
Implementing a transition towards sustainable patterns of energy consumption in the extractive sector, including energy efficiency and renewable energy sources, is an ongoing, but incipient, process in South America. The focus here is on social representations of elites on sustainable energy consumption in the large-scale mining sector in Argentina, Chile, Colombia and Ecuador. The concepts of efficiency and non-conventional renewable energy are widely accepted. The main question is: are elite views in these countries favourable to energy transition and energy-sustainable industrial consumption in the extractive sector? Notwithstanding a basic consensus, different views exists on renewable and efficient energy, regulations and policies. In the semantic core of the discourses, the different and contradictory interpretations of elite groups are evident. A qualitative discourse analysis and a descriptive statistics comparison of these differences reveal shifts in meaning, in social positions, and the influence of each country context in the production of these discourses. © 2018, Universidade Estadual de Campinas.; A transição para padrões sustentáveis de energia no sector extrativo, incluindo eficiência energética e fontes de energia renováveis, é um processo contínuo, mas incipiente, na América do Sul. O foco aqui é sobre as representações sociais das elites sobre "consumo de energia sustentável" no setor de mineração em larga escala na Argentina, Chile, Colômbia e Equador. Os conceitos de eficiência e energia renovável não convencional são amplamente aceitos. A principal questão é: são as opiniões das elites desses países favoráveis à transição energética no sector extrativo? Apesar do consenso básico, existem diferentes discursos sobre regulamentos e políticas de energia renováveis e eficientes. No núcleo semântico dos discursos, as interpretações diferentes e contraditórias dos grupos de elite são evidentes. Uma análise qualitativa do discurso e uma comparação estatística descritiva dessas diferenças revelam mudanças no sentido, nas posições sociais e na influência do contexto de cada país na produção desses discursos. © 2018, Universidade Estadual de Campinas.; La transición hacia patrones sustentables de energía en el sector extractivo es un proceso incipiente en América del Sur. Se analizan aquí las representaciones sociales de las élites en el "consumo de energía sustentable", en el sector minero a gran escala en Argentina, Chile, Colombia y Ecuador. Los conceptos de eficiencia y energía renovable no convencional son ampliamente aceptados. La pregunta principal es: ¿son las opiniones de las élites en estos países favorables a la transición energética en el sector extractivo? A pesar del básico consenso, existen diferentes discursos sobre regulaciones y políticas energéticas renovables y eficientes. En el núcleo semántico de sus discursos, emergen visiones diferentes y contradictorias. Un análisis del discurso y una estadística descriptiva de esas diferencias revelan cambios en el significado, en las posiciones sociales, y de la influencia del contexto de cada país en la producción de esos discursos. © 2018, Universidade Estadual de Campinas.